Effects of varying concentrations of alanine, glutamine, glycine and valine on amino acid transport and intracellular metabolism in mammary epithelial cells - Hruby, A. C.; Teixeira, I. A. M. A. [UNESP]; Yoder, P. S.; Hanigan, M. D.; Chizzotti, M. L. (Wageningen Acad Publ, 2019)
The objective of this study was to evaluate the effects of varying concentrations of the main non-essential amino acids (NEAA) involved in bi-directional transport, Ala, Gln, and Gly, on uptake of Val and other branched-chain amino acids (BCAA) by mammary epithelial cells. A cell culture trial was conducted with four treatments representing high and low concentrations of AA known to be involved in efflux transport. The bi-directional transport of BCAA was affected by varying Val, Ala, Gln, and Gly concentrations, indicating competition for AA transporters.
Keywords: bi-directional transport; cell culture; in vitro; stable-isotope